Preparation method and application of efficient antibacterial starch grafted copolymer nanofiber drug-loaded membrane

By grafting and branching chains on the starch molecular chain and preparing the starch graft copolymer nanofiber drug-loading film by electrospinning, the problems of high water swelling and lack of antibacterial properties of the pure starch nanofiber membrane are solved, and the long-term sustained release and efficient antibacterial effects of the drug are achieved.

CN119770462AActive Publication Date: 2025-04-08ANHUI POLYTECHNIC UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411979043.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the prior art, the pure starch nanofiber membrane prepared by electrospinning has high water swelling, resulting in rapid dispersion of the drug, poor sustained release performance of the drug, and lacks antibacterial properties, making it impossible to achieve the long-term sustained release and antibacterial effects of the drug.

Method used

Starch grafting copolymers are prepared by grafting on the starch molecular chain that can exhibit "remote effect", and a starch graft copolymer nanofiber drug-loading film is prepared by electrospinning method. Combining the antibacterial properties and electrostatic power of the grafting branch chain, the drug sustained release effect and antibacterial effect of the drug-loading film are improved.

Benefits of technology

It significantly improves the drug sustained release effect and antibacterial effect of the drug-loading membrane, realizes long-term release and continuous administration of the drug, is suitable for the treatment of chronic diseases, and provides efficient antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770462A_ABST
    Figure CN119770462A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient antibacterial starch graft copolymer nanofiber drug-loaded membrane as well as a preparation method and application thereof, belongs to the field of biomedicine, and particularly relates to a preparation method of the efficient antibacterial starch graft copolymer nanofiber drug-loaded membrane by taking high-amylose corn starch as a raw material and adopting a Fe < 2 + >-H2O2 redox system. Two monomers of hydroxybutyl acrylate and (3-acrylamidopropyl) trimethyl ammonium chloride are grafted to high amylose corn starch to prepare an amphiphilic starch grafted copolymer, and the starch grafted copolymer nanofiber drug-loaded membrane is prepared by electrostatic spinning. According to the starch grafted copolymer nanofiber drug-loaded membrane prepared by the invention, the starch grafted copolymer has good compatibility with the drug, the cumulative release rate of the drug is obviously reduced, the drug release time is longer, and long-time release and continuous administration of the drug can be realized; the drug-loaded membrane also has excellent antibacterial property, higher porosity and higher water vapor permeability, can provide better air permeability and oxygen permeability when being used as an external dressing, and can be applied to sustained-release drugs or medical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine, and specifically discloses a preparation method and application of a highly effective antibacterial starch graft copolymer nanofiber drug-carrying film. Background Art

[0002] In recent years, with the rapid economic development, the oil resources are becoming increasingly scarce, the price continues to soar, and a series of major environmental pollution problems caused by the processing and preparation of various polymer materials with petrochemical products as the main raw materials have prompted the application research of corn starch, a natural polymer material with low price, natural renewable, good environmental performance, degradable, and in line with the requirements of environmental protection and sustainable development strategies, to be increasingly valued by people. It is widely used in the fields of textile warp sizing, papermaking, food, plastics and medicine. However, there are a large number of glucose ring structures in starch macromolecules, which makes the starch film present the characteristics of "hard and brittle"; starch molecules contain a large number of hydroxyl groups, and there are hydroxyl groups on carbons 2, 3, and 6 on each glucose unit, forming a large number of hydrogen bonds within and between molecules. Even if the force of hydrogen bonds themselves is weak, due to the huge number of hydrogen bonds, the connection between molecules is very tight, and the molecular movement is difficult, resulting in poor processability of starch. All these seriously affect the application effect of starch in the above fields.

[0003] At present, some scholars have conducted relevant research on the preparation of starch nanofiber membranes by electrospinning. However, pure starch fiber membranes prepared by electrospinning still have certain defects, such as high water swelling, which causes the drug to be easily dispersed into water quickly due to the high water swelling of starch nanofibers when used as drug carriers, showing poor drug sustained release performance and unable to achieve long-term sustained release of drugs. In addition, pure starch fiber membranes do not have antibacterial properties. When loaded with anti-inflammatory and analgesic drugs (such as aspirin), the drug-loaded membranes formed do not have antibacterial properties. Summary of the invention

[0004] The technical problem to be solved by the present invention is to address the deficiencies in the prior art and to provide a method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film and its application, wherein grafted side chains that can exhibit "remote action" are connected to starch molecular chains to prepare starch grafted polymers; the antibacterial properties of the grafted side chains and the electrostatic force generated between the grafted side chains and the drugs are utilized to overcome the performance problems existing in the preparation of pure starch nanofiber drug-loaded films by electrospinning, thereby significantly improving the drug sustained-release effect and antibacterial effect of the drug-loaded film.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film, comprising the following steps:

[0006] (1) Preparation of starch graft copolymers: By using Fe2+ -H2O2 redox system, two monomers, hydroxybutyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride, were grafted onto high-amylose corn starch to prepare starch graft copolymers;

[0007] (2) Electrospinning starch graft copolymer nanofiber drug-loaded film: The starch graft copolymer prepared in step (1) is dissolved in a polar organic solvent to form a starch graft copolymer solution, the drug to be loaded is added to the starch graft copolymer solution, the solution is heated to 50-90° C. and stirred until the solution becomes transparent to obtain a spinning solution, and the spinning solution is electrospun to obtain a starch graft copolymer nanofiber drug-loaded film.

[0008] As a further description of the above technical scheme, step (1) is specifically as follows: adding high-amylose corn starch to an alcohol-water mixture to prepare starch milk, adjusting the pH of the starch milk to 3-4, and under nitrogen protection, simultaneously adding hydroxybutyl acrylate, (3-acrylamidopropyl)trimethylammonium chloride, an aqueous solution of ammonium ferrous sulfate and an aqueous solution of hydrogen peroxide to the starch milk within 30-40 minutes, and continuously reacting at 30-40° C. for 4-8 hours in an anaerobic state, adjusting the pH to 6-7, filtering, washing and crushing the filter cake and then drying to obtain a starch graft copolymer.

[0009] As a further description of the above technical solution, the volume ratio of alcohol to water in the alcohol-water mixture is (3-5):1, and the mass fraction of starch milk is 20-40%.

[0010] As a further description of the above technical solution, the mass fraction of the aqueous ammonium ferrous sulfate solution is 0.5%, and the mass fraction of the aqueous hydrogen peroxide solution is 0.1%.

[0011] As a further description of the above technical solution, the organic solvent is dimethyl sulfoxide, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine or chloroform.

[0012] As a further description of the above technical solution, the drug to be loaded in step (2) is a drug that needs to be sustained-released, such as some drugs for treating chronic diseases, and the amount of the drug added is 8-15% of the mass of the starch graft copolymer. Specifically, the drug to be loaded is aspirin, ibuprofen, acetaminophen, benolate or indomethacin.

[0013] The present invention also provides the use of this highly effective antibacterial starch graft copolymer nanofiber drug-loaded film in a drug sustained-release system or medical material. The drug sustained-release system includes but is not limited to some sustained-release drugs for anti-inflammatory, analgesic, antipyretic and chronic disease treatment, and the medical material includes but is not limited to some sustained-release drug dressings for treating trauma.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) In the nanofiber drug-loaded film prepared by the present invention, the starch graft copolymer has good compatibility with the drug;

[0016] (2) Compared with the drug-loaded film directly prepared from starch, the nanofiber drug-loaded film prepared from starch graft copolymer of the present invention has a significantly lower cumulative drug release rate, a more sustained drug release time, and can achieve long-term drug release and continuous drug administration, and can be used to treat some chronic diseases that are difficult to eradicate at one time, such as cardiovascular disease, cancer, diabetes, etc.;

[0017] (3) The starch graft copolymer nanofiber drug-loaded film also has a high porosity and a strong water vapor permeability. When used as a wound dressing, it can provide the wound with better air permeability and oxygen permeability, which is beneficial to wound healing.

[0018] (4) The introduction of two grafted monomer units makes starch hydrophilic, thereby enhancing the binding effect between starch and water molecules and increasing the swelling rate, so that the nanofiber drug-loaded film is less affected in the human body or in different environments. That is, the starch graft copolymer nanofiber drug-loaded film prepared by the present invention has strong environmental stability;

[0019] (5) The present invention connects (3-acrylamidopropyl)trimethylammonium chloride monomer to starch to achieve bactericidal and antibacterial effects. Compared with the nanofiber drug-loaded film prepared using starch, the nanofiber drug-loaded film prepared using starch graft copolymer in the present invention has excellent antibacterial properties, and the antibacterial rate basically reaches 100%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a molecular structure diagram of the prepared starch graft copolymer;

[0021] Figure 2 are SEM images of sample 1, sample 2, sample 3, and sample 0;

[0022] Figure 3 This is the standard curve for aspirin;

[0023] Figure 4 is the drug cumulative release rate graph of the nanofiber drug-loaded membrane of sample 1, sample 2, sample 3 and sample 0;

[0024] Figure 5 is the porosity bar graph of the nanofiber drug-loaded membranes of sample 1, sample 2, sample 3, and sample 0;

[0025] Figure 6 is the contact angle of the nanofiber drug-loaded films of sample 1, sample 2, sample 3, and sample 0;

[0026] Figure 7 is a bar graph of the swelling rate results of the nanofiber drug-loaded films of sample 1, sample 2, sample 3 and sample 0;

[0027] Figure 8 It is a bar graph of the water vapor permeability results of the nanofiber drug-loaded films of sample 1, sample 2, sample 3 and sample 0.

[0028] Fig. 9 is the antibacterial effect diagram of the nanofiber drug-loaded membrane of sample 0 and sample 3 on E.coil;

[0029] Fig.10 This is a graph showing the antibacterial effect of the nanofiber drug-loaded films of samples 0 and 3 on S. aureus. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific implementation modes.

[0031] Example 1

[0032] This embodiment provides a method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film, comprising the following steps:

[0033] (1) Preparation of starch graft copolymers: By using Fe 2+ -H2O2 redox system, two monomers, hydroxybutyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride, were grafted onto high-amylose corn starch to prepare starch graft copolymers, specifically:

[0034] Weigh 120g of high-amylose corn starch by dry weight, add it to an alcohol-water mixture with a volume ratio of 3:1 to prepare a starch milk with a mass fraction of 20%, adjust the pH to 3-4 with dilute hydrochloric acid, transfer to a four-necked flask and stir thoroughly. After heating to 40°C in a water bath, introduce nitrogen for 30 minutes and under nitrogen protection, simultaneously add 40g of hydroxybutyl acrylate, 20g of (3-acrylamidopropyl)trimethylammonium chloride, 0.5% ammonium ferrous sulfate, and 1.0% aqueous hydrogen peroxide solution in the required amount to the starch milk, and the addition is required to be completed within 30-40 minutes, and then continue the anaerobic reaction for 4 hours. Use 6% sodium carbonate solution to adjust the pH of the grafted product to 6-7, filter and wash several times, then crush the filter cake and dry it in an oven and bag it for later use to obtain a starch graft copolymer with a molecular structure such as Figure 1 As shown, the grafting rate of the starch graft copolymer is 17.08%.

[0035] (2) Electrospinning starch graft copolymer nanofiber drug-loaded film:

[0036] A certain amount of the starch graft copolymer prepared in step (1) is weighed, and the starch graft copolymer is dissolved in dimethyl sulfoxide, wherein the mass fraction of the starch graft copolymer is 15%, and aspirin, a drug to be sustained-release, is added in an amount of 8% by mass of the starch graft copolymer, and the solution is heated to 50° C. and stirred with a magnetic stirrer until the solution becomes transparent, and allowed to stand until degassing to obtain a spinning solution; the spinning environment temperature of the electrospinning equipment is adjusted to 60° C., the voltage is 20 kV, the distance between the syringe and the roller is 15 cm, and the propulsion speed is 1 mL / h, and the spinning solution is electrospun to obtain a starch graft copolymer nanofiber drug-loaded film, which is recorded as sample 1.

[0037] Example 2

[0038] This embodiment provides a method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film, comprising the following steps:

[0039] (1) Preparation of starch graft copolymers:

[0040] Weigh 120g of high-amylose corn starch by dry weight, add it to an alcohol-water mixture with a volume ratio of 5:1 to prepare a starch milk with a mass fraction of 40%, adjust the pH to 3-4 with dilute hydrochloric acid, transfer to a four-necked flask and stir thoroughly. After heating to 40°C in a water bath, introduce nitrogen for 30 minutes and under nitrogen protection, simultaneously add 40g of hydroxybutyl acrylate, 30g of (3-acrylamidopropyl)trimethylammonium chloride, 0.5% ammonium ferrous sulfate, and 1.0% aqueous hydrogen peroxide solution in the required amount to the starch milk, and the addition is required to be completed within 30-40 minutes, and then continue the anaerobic reaction for 5 hours. Use 6% sodium carbonate solution to adjust the pH of the grafted product to 6-7, filter and wash several times, then crush the filter cake and dry it in an oven and bag it for later use to obtain a starch graft copolymer with a molecular structure such as Figure 1 As shown, the grafting rate of the starch graft copolymer is 23.17%.

[0041] (2) Electrospinning starch graft copolymer nanofiber drug-loaded film:

[0042] A certain amount of the starch graft copolymer prepared in step (1) was weighed, and the starch graft copolymer was dissolved in dimethyl sulfoxide, wherein the mass fraction of the starch graft copolymer was 40%, and aspirin was added in an amount of 15% by mass of the starch graft copolymer. The solution was heated to 90° C. and stirred with a magnetic stirrer until the solution became transparent, and allowed to stand until degassing to obtain a spinning solution. The spinning environment temperature of the electrospinning equipment was adjusted to 60° C., the voltage was 20 kV, the distance between the syringe and the roller was 15 cm, and the propulsion speed was 1 mL / h. The spinning solution was electrospun to obtain a starch graft copolymer nanofiber drug-loaded film, which was recorded as sample 2.

[0043] Example 3

[0044] This embodiment provides a method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film, comprising the following steps:

[0045] (1) Preparation of starch graft copolymers:

[0046] Weigh 120g of high-amylose corn starch by dry weight, add it to an alcohol-water mixture with a volume ratio of 4:1 to prepare a starch milk with a mass fraction of 30%, adjust the pH to 3-4 with dilute hydrochloric acid, transfer to a four-necked flask and stir thoroughly. After heating to 30°C in a water bath, introduce nitrogen for 30 minutes and under nitrogen protection, simultaneously add 40g of hydroxybutyl acrylate, 40g of (3-acrylamidopropyl)trimethylammonium chloride, 0.5% ammonium ferrous sulfate, and 1.0% aqueous hydrogen peroxide solution in the required amount to the starch milk, and the addition is required to be completed within 30-40 minutes, and then continue the anaerobic reaction for 6 hours. Use 6% sodium carbonate solution to adjust the pH of the grafted product to 6-7, filter and wash several times, crush the filter cake, dry it in an oven and bag it for later use, and obtain a starch graft copolymer with a molecular structure such as Figure 1 As shown, the grafting rate of the starch graft copolymer is 27.99%.

[0047] (2) Electrospinning starch graft copolymer nanofiber drug-loaded film:

[0048] Weigh a certain amount of the starch graft copolymer prepared in step (1), dissolve the starch graft copolymer in dimethyl sulfoxide, the mass fraction of the starch graft copolymer is 18%, add aspirin in an amount of 10% by mass of the starch graft copolymer, heat to 70°C and stir with a magnetic stirrer until the solution becomes transparent, let it stand until degassing, and obtain a spinning solution; adjust the spinning environment temperature of the electrospinning equipment to 60°C, the voltage to 20 kV, the distance between the syringe and the roller to 15 cm, the propulsion speed to 1 mL / h, and electrospin the spinning solution to obtain a starch graft copolymer nanofiber drug-loaded film, which is recorded as sample 3.

[0049] Comparative Example:

[0050] This comparative example provides a method for preparing a starch nanofiber drug-loaded film, specifically:

[0051] A certain amount of high-amylose corn starch was weighed, and the high-amylose corn starch was dissolved in dimethyl sulfoxide, the mass fraction of the high-amylose corn starch was 18%, and aspirin was added at 10% by mass of the starch. The solution was heated to 70°C and stirred with a magnetic stirrer until the solution became transparent. The solution was allowed to stand until degassing to obtain a spinning solution. The spinning environment temperature of the electrospinning equipment was adjusted to 60°C, the voltage was 20 kV, the distance between the syringe and the roller was 15 cm, and the propulsion speed was 1 mL / h. The spinning solution was electrospun to obtain a starch nanofiber drug-loaded film, which was recorded as sample 0.

[0052] Performance Test:

[0053] 1. SEM morphology characterization:

[0054] SEM can observe the morphological structure of the surface of nanofiber drug-loaded membrane, including the shape, size, and arrangement of the fibers. SEM analysis of electrospun nanofiber drug-loaded membrane can intuitively understand the morphological characteristics of the fibers, evaluate the uniformity, density, and arrangement of the fibers, and provide a morphological basis for subsequent performance testing and application. Figure 2 The SEM images of the nanofiber drug-loaded films (sample 0, sample 1, sample 2 and sample 3) prepared using high amylose starch and three kinds of starch graft copolymers are shown in Figure 1. Figure 2 It can be seen that the nanofiber surfaces of the four drug-loaded films are basically smooth, with no obvious polymer particles remaining, indicating that high-amylose starch and the three starch graft copolymers have good compatibility with aspirin.

[0055] 2. Drug sustained release performance test:

[0056] Generally speaking, in order to treat some chronic diseases that are difficult to eradicate at one time, such as cardiovascular disease, cancer, diabetes, etc., in order to achieve long-term drug release and continuous drug administration, nanofiber drug-loaded membranes with a lower sustained release rate will be the best choice.

[0057] 2.1 Preparation of phosphate (PBS) sustained-release solution: weigh 8.0 g NaCl, 0.2 g KCl, 1.44 g Na2HPO4, and 0.24 g KH2PO4 and dissolve them in 800 mL distilled water. Use HCl to adjust the solution to 7.4, and finally add distilled water to make up to 1 L to obtain a 0.01 mol / L PBS sustained-release solution.

[0058] 2.2 Draw an aspirin standard curve: Weigh appropriate amounts of aspirin and dissolve them in PBS sustained-release solution to obtain standard solutions of 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L, 30 mg / L and 35 mg / L, respectively. Use an ultraviolet spectrophotometer to test the full-wavelength absorbance of these standard solutions, and then measure the absorbance at a wavelength of 296 nm. Use the absorbance as the y-axis and the aspirin solution concentration as the x-axis to draw an aspirin standard curve, as shown in the figure. Figure 3 As shown by Figure 3 It can be seen that when the aspirin concentration is in the range of 5 to 100 mg / L, the absorbance and concentration show a good linear relationship. The standard curve equation is y=0.0152x-0.0233, and the correlation coefficient R 2 It is 0.9941.

[0059] 2.3 Test the sustained-release performance of the samples: Take 100 mL of PBS sustained-release solution, cut and weigh the nanofiber drug-loaded films of sample 1, sample 2, sample 3 and sample 0 of the same mass, put them into the PBS sustained-release solution and keep the constant temperature at 37°C, take out 6 mL of PBS sustained-release solution at 1 h, 2 h, 3 h, 6 h and 9 h respectively, and measure its absorbance at a wavelength of 296 nm with an ultraviolet spectrophotometer. Every time 6 mL of PBS sustained-release solution is taken out, 6 mL of PBS sustained-release solution is added at the same time. The cumulative release amount of the drug is calculated according to the aspirin standard curve, and then the cumulative release rate curves of aspirin drugs of the four samples are drawn, as shown in FIG. Figure 4 shown.

[0060] 2.4 Analysis of sustained release performance results: Figure 4 It can be seen that the cumulative release rate of sample 0 prepared with high amylose starch is close to 40% after 2 hours, while the cumulative drug release rates of samples 1, 2 and 3 prepared with starch graft copolymers are significantly lower than that of sample 0, and the sustained release rate of aspirin in sample 3 is the lowest and the drug release time is the longest. Sample 3 has a large number of positively charged cations, which can electrostatically adsorb the negatively charged aspirin drug, thereby hindering the release of the drug aspirin, reducing the cumulative release rate of aspirin, and significantly improving the drug sustained release effect of the drug-loaded film.

[0061] 3. Porosity test:

[0062] Porosity is an important parameter for wound dressings in practical applications. The ideal porosity value of wound dressings should be between 60% and 90% to provide better air permeability and oxygen penetration to the wound.

[0063] 3.1 Porosity test process: Cut 3cm×3cm nanofiber drug-loaded films of sample 1, sample 2, sample 3 and sample 0 respectively, and let them stand at room temperature to achieve a humidity equilibrium state equivalent to the environment to prevent water evaporation or absorption from causing changes in the porosity of the sample. Use an electronic balance to accurately weigh the weight of the cut sample 1, sample 2, sample 3 and sample 0, and record them as m0. Place the weighed samples in ethanol solution respectively and soak them completely for 1 hour. Then take out the soaked samples and wipe off the excess solution on the surface with a paper towel. Use an electronic balance to accurately weigh the weight of the treated samples again and record them as m1. Use the following formula to calculate the porosity (p, %) of the sample and draw a porosity graph, as shown below: Figure 5 As shown:

[0064]

[0065] 3.2 Porosity analysis: Figure 5It can be seen that with the increase of grafting rate, the porosity gradually increases. The main reason is that with the increase of grafting rate, the lower the average fiber diameter, the larger the specific surface area of ​​the drug-loaded membrane, and the higher the porosity.

[0066] 4. Water contact angle test:

[0067] Water contact angle test can be used to evaluate the surface properties of nanofiber drug-loaded membranes. Nanofiber drug-loaded membranes are usually used as drug release systems or medical materials. The stability of their surface is crucial to their functions and performance. Generally speaking, hydrophilic nanofiber drug-loaded membranes have a faster sustained release rate of drugs. On the contrary, appropriately reducing the hydrophilicity is more conducive to reducing the release rate of drugs, thereby achieving long-term stable release of drugs from drug-loaded membranes.

[0068] 4.1 Water contact angle test process: Cut 5×5 mm square pieces from sample 1, sample 2, sample 3 and sample 0 respectively. 2 The nanofiber drug-loaded film sample is fixed on the edge of the slide. After adjusting the stage height and making the slide horizontal, a water drop is dripped vertically onto the center surface of the sample. A front view of the liquid just touching the sample is taken, as shown in Figure 2. Figure 6 As shown, the baseline is adjusted and the contact angles of sample 1, sample 2, sample 3 and sample 0 are calculated.

[0069] 4.2 Water contact angle test results: Figure 6 It can be seen that the water contact angles of the nanofiber drug-loaded films of sample 1, sample 2, sample 3 and sample 0 are all less than 90°, which are 33.94°, 48.91°, 41.41° and 22.62° respectively. With the increase of the grafting rate, the water contact angle of the drug-loaded film decreases slightly. This is because with the increase of the grafting rate, the number of hydrophilic cationic groups increases, which increases the hydrophilicity of the drug-loaded film to a certain extent; in addition, with the increase of the grafting rate, the fiber diameter decreases, the specific surface area increases, and the porosity increases, thereby improving the interfacial water adsorption capacity of the nanofiber drug-loaded film.

[0070] 5. Swelling performance test:

[0071] Swelling performance testing can help evaluate the stability of drug-loaded films under different solution conditions. Drug sustained-release systems may be affected by different solution environments in the human body or the environment, such as different pH values, temperatures, or solution components. By simulating these conditions and testing the swelling performance of drug-loaded films, their stability and reliability in practical applications can be evaluated.

[0072] 5.1 Swelling performance test process: Sample 1, sample 2, sample 3 and sample 0 were cut into 2cm×2cm sizes respectively, and left to stand at 25℃ and relative humidity of 65% for 24h. The cut samples 1, sample 2, sample 3 and sample 0 were weighed respectively, recorded as m0. Sample 1, sample 2, sample 3 and sample 0 were placed in a PBS sustained-release solution 40 times of their own mass, and left in a 37℃ oven for 24h to reach saturation. After being suspended for 30s, the wet weights of sample 1, sample 2, sample 3 and sample 0 were weighed respectively, recorded as m1. The swelling rates of sample 1, sample 2, sample 3 and sample 0 were calculated according to the following formulas, and the swelling rate graphs were drawn, as shown in the figure below: Figure 7 As shown:

[0073]

[0074] 5.2 Swelling performance test results: Figure 7 It can be seen that with the increase of grafting rate, the swelling rate of drug-loaded film shows a trend of gradual increase. The reason may be the introduction of two grafted monomer units, which makes the starch hydrophilic as a whole. As a result, with the increase of grafting rate, the hydrophilicity is enhanced, which enhances the binding effect between starch and water molecules and increases the swelling rate of drug-loaded film.

[0075] 6. Water vapor transmission rate test:

[0076] The significance of testing the water vapor permeability of nanofiber drug-loaded membranes is to evaluate their air permeability during application. Water vapor permeability refers to the rate at which water vapor passes through a material per unit time, and is one of the important indicators for measuring the air permeability of a material. Air permeability can affect the release rate and release behavior of drugs in drug-loaded membranes, thereby affecting the efficacy and treatment effect of the drugs.

[0077] 6.1 Water vapor transmission rate test process: 10mL phosphate buffer was placed in a cylindrical glass bottle. Sample 1, sample 2, sample 3 and sample 0 were cut into a size (S) approximately equal to the cross-sectional area of ​​the container mouth. The container mouth was covered with the cut-out drug film and then sealed with tape and weighed as m0. An open glass bottle containing 10mL phosphate buffer was used as a blank control group. After that, the entire device was placed in a 37℃ oven to maintain relatively low humidity conditions. It was taken out and weighed every hour and recorded as m0. n , twice in total, calculate the water vapor transmission rates of sample 1, sample 2, sample 3 and sample 0 respectively according to the following formula, and draw the transmission rate graph, such as Figure 8 As shown:

[0078]

[0079] Where: T is the interval between two times of mass reduction, S is the area of ​​the glass bottle mouth (0.000706m2 ).

[0080] 6.2 Water vapor transmission rate test results: Figure 8 It can be seen that the water vapor permeability first decreases and then increases with the increase of the grafting rate of the starch graft copolymer. This is because the porosity is positively correlated with the water vapor permeability, that is, the higher the porosity, the faster the rate at which water vapor passes through the drug-loaded film per unit time.

[0081] 7. Antibacterial performance test:

[0082] 7.1 Bacterial culture: Use an inoculation loop to scrape a sufficient amount of bacteria and place it in a glass tube containing 5 mL of liquid culture medium (Broth). Vortex to evenly disperse the bacteria and shake the glass tube in a constant temperature shaker at 37°C (120r / min). After culturing the bacteria for 18 to 24 hours, separate the bacteria by centrifugation and wash the dispersed bacteria with 5 mL of PBS sustained release solution. Finally, add the evenly dispersed 0.1 mL of bacteria / PBS suspension to a new glass tube containing Broth and place it in an oscillating box to continue constant temperature culture. This is the first generation of bacteria. According to the above method, multiply the bacteria for three generations and set aside. The inoculation concentration of E.coil bacteria is 5.7×10 6 CFU / sample, the inoculation concentration of S. aureus was 2.5×10 6 CFU / sample.

[0083] 7.2 Antibacterial performance test process: Cut sample 0 and sample 3 into 2.5cm×2.5cm size respectively, place the samples on the surface of the culture dish on the sterile operation platform, and add 25μL of pre-cultured bacterial suspension respectively; cover the other sample on top to ensure that the bacterial solution is fully in contact with the sample, wait for 5 minutes, put the two samples into 5mL of PBS sustained-release solution, vortex the solution for 10s, and then use 100mmol / L PBS sustained-release solution for continuous dilution and evenly add it to the surface of the solid culture dish. After culturing in a 37℃ constant temperature incubator for 24h, the number of colonies is measured and the antibacterial rate is calculated. The blank sample operation is the same as the above experimental sample, and the antibacterial rate of the sample is calculated using the following formula:

[0084]

[0085] Where: N1 is the number of bacterial colonies in the sample; N0 is the number of bacterial colonies in the blank sample.

[0086] 7.3 Antibacterial performance test results: The antibacterial effects of sample 0 and sample 3 are as follows: Fig. 9 , Fig.10 As shown in the figure, it can be seen that the drug-loaded film (sample 0) prepared directly using high-amylose corn starch has very poor antibacterial activity against both bacteria ( Fig. 9a. Fig.10 a), while the drug-loaded film (sample 3) prepared by grafting starch graft copolymer has excellent antibacterial properties, and the antibacterial rate against both bacteria is basically 100% ( Fig. 9 b, Fig.10 b), the reason may be that the starch graft copolymer contains a large number of positively charged cationic (3-acrylamidopropyl) trimethylammonium chloride monomer units. The positively charged cationic monomer units can produce strong electrostatic effects with the negatively charged anionic sites on the bacterial cell wall, leading to cell lysis and death, making the drug-loaded film exhibit a highly efficient antibacterial effect.

[0087] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. A person skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the present invention.

Claims

1. A method for preparing a highly effective antibacterial starch graft copolymer nanofiber drug-loaded film, characterized in that: The following steps are involved: (1) Preparation of starch graft copolymers: By using Fe 2+ -H2O2 redox system, two monomers, hydroxybutyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride, were grafted onto high-amylose corn starch to prepare starch graft copolymers; (2) Electrospinning starch graft copolymer nanofiber drug-loaded film: The starch graft copolymer prepared in step (1) is dissolved in a polar organic solvent to form a starch graft copolymer solution, the drug to be loaded is added to the starch graft copolymer solution, the solution is heated to 50-90° C. and stirred until the solution becomes transparent to obtain a spinning solution, and the spinning solution is electrospun to obtain a starch graft copolymer nanofiber drug-loaded film.

2. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 1, characterized in that: The step (1) is specifically as follows: adding high-amylose corn starch to an alcohol-water mixture to prepare starch milk, adjusting the pH of the starch milk to 3-4, and simultaneously dropping hydroxybutyl acrylate, (3-acrylamidopropyl)trimethylammonium chloride, an aqueous solution of ammonium ferrous sulfate and an aqueous solution of hydrogen peroxide into the starch milk under nitrogen protection within 30-40 minutes, continuously reacting at 30-40° C. for 4-6 hours in an anaerobic state, adjusting the pH to 6-7, filtering, washing, crushing the filter cake and drying to obtain a starch graft copolymer.

3. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 2, characterized in that: The volume ratio of alcohol to water in the alcohol-water mixture is (3-5):

1.

4. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 2 or 3, characterized in that: The mass fraction of starch milk is 20-40%.

5. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 2, characterized in that: The mass fraction of the aqueous ammonium ferrous sulfate solution is 0.5%, and the mass fraction of the aqueous hydrogen peroxide solution is 0.1%.

6. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 1, characterized in that: The organic solvent in step (2) is dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine or chloroform.

7. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 1, characterized in that: The drug to be loaded in step (2) is a drug that needs to be sustained-released, and the added amount of the drug to be loaded is 8-15% of the mass of the starch graft copolymer.

8. The method for preparing the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 7, characterized in that: The drug to be loaded is aspirin, ibuprofen, acetaminophen, benolate or indomethacin.

9. Use of the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film prepared by the method according to any one of claims 1 to 8 in sustained-release drugs or medical materials.

10. Use of the highly effective antibacterial starch graft copolymer nanofiber drug-loaded film according to claim 9 in sustained-release drugs or medical materials, characterized in that: The sustained-release drugs include drugs for anti-inflammatory, analgesic, antipyretic or chronic disease treatment, and the medical materials include external sustained-release dressings.

Citation Information

Patent Citations

  • Preparation method and application of starch grafted double-block polymer slurry with grafted branch chain composed of hydrophilic block and hydrophobic block

    CN113698557A

  • Starch-based nanofiber membrane as well as preparation method and application thereof

    CN118374904A

  • A biocompatible adhesive system and a bioadhesive drug delivery system with controllable release

    WO2000047644A1